Comparative effectiveness of high-intensity interval training and moderate-intensity continuous training on cardiometabolic health in patients with diabesity: a systematic review and meta-analysis of randomized controlled trials - Sameer Badri Al-Mhanna; Eric Tsz-Chun Poon; Barry A. Franklin; Mark A. Tarnopolsky; John A. Hawley; John M. Jakicic; Emmanuel Stamatakis; Jonathan P. Little; Linda S. Pescatello; Deborah Riebe; Walter R. Thompson; James S. Skinner; et al. (Diabetology & Metabolic Syndrome)
Abstract Objective To evaluate the effects of high-intensity interval training (HIIT) on cardiometabolic health-related outcomes in patients with type 2 diabetes mellitus and concurrent overweight/obesity (diabesity). Design Systematic review and meta-analysis of randomized controlled trials (RCTs). Data sources PubMed, Web of Science, Scopus, Science Direct, Cochrane Library, and Google Scholar databases were searched from inception up to January 31, 2025. Eligibility criteria for selecting studies RCTs comparing HIIT alone ≥ 2 weeks in duration with moderate-intensity continuous training (MICT). Participants were adults with diabesity. Results A total of 26 RCTs qualified, involving 790 patients (50/50 female/male ratio; age: 59.8 ± 12.9 years; body mass index: 28.9 ± 4.2 kg/m2). HIIT revealed a significant reduction in fasting insulin [standardized mean differences (SMD) − 0.43, 95% CI − 0.82 to − 0.05] and homeostatic model assessment for insulin resistance (HOMA-IR; SMD − 0.52, 95% CI − 0.97 to − 0.07) compared to MICT. Additionally, HIIT significantly increased cardiorespiratory fitness (VO₂max; SMD 0.53, 95% CI 0.14 to 0.91) compared to MICT. Other clinically relevant cardiometabolic outcomes, including body composition, lipid profile, fasting blood glucose, glycated hemoglobin, and blood pressure, showed comparable changes between HIIT and MICT. Subgroup analyses of studies reporting comorbidities indicated a significant increase in high-density lipoprotein cholesterol (SMD 0.49, 95% CI 0.04 to 0.95) and a decrease in HOMA-IR (SMD − 0.83, 95% CI − 1.62 to − 0.04) for HIIT compared to MICT. However, these findings are limited by very low certainty evidence and non-robust sensitivity analyses. Conclusions The present findings suggest that HIIT may serve as an adjunctive non-pharmaceutical management solution for patients with diabesity. Open Science Framework registry: https://osf.io/9by24